PENGARUH PERENCANAAN PAJAK, STRUKTUR MODAL DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Wahyuni, Tri; Wizanasari, Wizanasari (Unversitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to analyze and examine the effect of tax planning, capital structure, and financial performance on firm value. The method used in this study is the quantitative method. The population in this study is Property Real Estate companies listed on the Indonesia Stock Exchange in 2017-2021 totaling 51 companies. The sample selection was selected using the purposive sampling method so that a total sample of 10 companies was obtained, but due to the outlier test in this study, the final sample became 8 companies. Data testing methods in this study are descriptive statistical analysis, classical assumptions, panel data regression analysis, and hypothesis testing. Based on the results of research that has been conducted using Eviews series 10 software, it shows that partially tax planning and capital structure do not affect company value, while financial performance affects company value. Simultaneously, tax planning, capital structure, and financial performance affect the value of the company.